To study the impact of psychiatry posting on attitude towards psychiatry and estimated likelihood of psychiatry as a career choice in female interns in North India - Garg, Sunny; Chauhan, Alka; Singh, Mahender; Khan, Mariya; Singh, Sanjeet; Bansal, Kirti (Asian Journal of Medical Sciences, 2020)
Background: Psychiatric disorders have been rising in last few years and emerging as leading cause of disease burden. Psychiatry as a discipline of medicine carry a lot of stigma due to which there is a lack of young medical students or professionals in choosing psychiatry as a career. Aims and Objectives: To study the impact of psychiatry posting on attitude towards psychiatry and estimation of likelihood of Psychiatry as a career choice in female interns. Materials and Methods: A cross sectional observational study of 112 female interns who met the Inclusion criteria. A written informed consent was obtained from the interns. A selfassessable ATP-30 scale was used to assess the attitude of the interns, this questionnaire was filled by the interns on the first day and after the two weeks of their posting in psychiatry department. The data collected was analysed with the help of SPSS version (21.0) info. Results: Ninety-eight interns were considered for further analysis because 14 female interns fulfilled the exclusion criteria. More than 95% interns reported to have positive attitude towards psychiatry throughout the posting. Results showed a statistically significant (<0.01) positive attitude towards major areas in psychiatry except only psychiatric hospitals and treatment. Only 33 female interns chose psychiatry as a career choice after the posting of two weeks which is not statistically significant, while around 40% interns denied for it. Conclusion: Interns showed highly positive attitude towards psychiatry. The positive attitude of interns towards psychiatry would go a long way towards reducing the stigma attached to people with mental illness and mental health professionals.